Relationship Between Knowledge and Adherence to Antihypertensive at Public Healthcare in Banjarmasin City, Indonesia - Hasniah, Hasniah; Hardiana, Hardiana; Rony, Rony; Fadillah, Aris; Erlianti, Karina; Ramadhani, Juwita (Pharmacology and Clinical Pharmacy Research, 2024)
Hypertension is one of the world’s most hazardous diseases since it harms the heart, brain, kidneys, and other organs. Patients’ understanding of hypertension can be the key to successful treatment. Nonadherence with antihypertensive medication is a primary cause of therapeutic failure and is considered a serious issue. The purpose of this study is to examine the association between antihypertensive knowledge and adherence at public healthcare facilities. This study employed a quantitative approach using a cross- sectional design. The purposive sampling technique determined the sample, resulting in 100 hypertensive respondents from Public Healthcare. Knowledge is the independent variable in data collection; adherence to antihypertensive medications is the dependent variable; and demographic variables are the confounding variable. We employed the HFQ (Hypertension Fact Questionnaire) and MMAS-8 (Modified Morisky Adherence Scale-8) questionnaires as data-gathering instruments. We conducted univariate, bivariate, and multivariate analyses on the data using SPSS. Based on the study’s findings, it is possible to conclude that there is a significant association between knowledge level and adherence with antihypertensive medicine use in public healthcare, with a p-value of 0.003. Comorbidities are a risk factor for hypertension that affects adherence, with a p-value of 0.007 and an OR of 0.801, indicating that patients are 0.801 times more likely to take their medicine